2008
DOI: 10.1007/s11104-008-9639-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of nitrous oxide emissions from an Australian irrigated dairy pasture

Abstract: Understanding spatial variability of emissions of nitrous oxide (N 2 O) is essential to understanding of N 2 O emissions from soils to the atmosphere and in the design of statistically valid measurement programs to determine plot, farm and regional emission rates. Two afternoon, 'snap-shot' experiments were conducted; one in the summer and one in the autumn of 2004, to examine the statistics and soil variables affecting the spatial variability of N 2 O emissions at paddock scale. Small, static chambers (mini-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 17 publications
3
39
0
Order By: Relevance
“…This relationship between soil NO − 3 and NH + 4 concentrations and N 2 O flux is also observed in similar studies (e.g. Turner et al, 2008). Our conclusion from the correlation analysis is that the high spatial variability of N 2 O flux across the grazed field is primarily due to the uneven distribution of nitrogen deposition in the form of animal waste.…”
Section: Correlation Between Soil Properties and N 2 O Fluxsupporting
confidence: 88%
“…This relationship between soil NO − 3 and NH + 4 concentrations and N 2 O flux is also observed in similar studies (e.g. Turner et al, 2008). Our conclusion from the correlation analysis is that the high spatial variability of N 2 O flux across the grazed field is primarily due to the uneven distribution of nitrogen deposition in the form of animal waste.…”
Section: Correlation Between Soil Properties and N 2 O Fluxsupporting
confidence: 88%
“…N 2 O fluxes are believed to be driven primarily by the availability of nitrogen compounds in the soils (ammonium and nitrate) (Davidson et al, 2000) as well as physical properties of the soil such as WFPS, aerobic extent, soil type, temperature and compaction (Ball et al, 2008;ButterbachBahl et al, 2013;Choudhary et al, 2002;Davidson et al, 2000;Turner et al, 2008). The collection of these data on a temporal/spatial scale which would allow these models to be applied is not often logistically possible or affordable.…”
Section: Gap Filling Of N 2 O Fluxesmentioning
confidence: 99%
“…In this study, the median (13.6 mg N m −2 d −1 ) and CV (143 %) of N 2 O fluxes measured in the tea field were all found to be higher than those in other agricultural systems, such as grasslands (Ambus and Christensen, 1994;Turner et al, 2008),winter wheat (Ball et al, 1997;Clemens et al, 1999;Mathieu et al, 2006), and summer maize (Clemens et al, 1999); the findings were similar to the results for the wet season reported by Fu et al (2015), predominantly because of the optimal conditions for soil microbe activity…”
Section: N 2 O Fluxes In the Tea Fieldmentioning
confidence: 47%
“…Accurate estimates of the amount and characteristics of N 2 O emissions are important prerequisites for reducing N 2 O emissions from agro-ecosystems (Akiyama et al, 15 2013;Ambuset al, 1994;Han et al, 2013;Kiese et al, 2003;Konda et al, 2008Konda et al, , 2010Lin and Han, 2009;Mosier et al, 1996Mosier et al, , 1998Turner et al, 2008). However, N 2 O is microbially mediated; it is produced via microbial processes of nitrification under aerobic conditions and denitrification under anaerobic conditions (Firestone and Davidson, 1989;Hayatsu, 1993;Mathieu et al, 2006;Venterea and Rolston, 2000; both the inherent complexities of N 2 O emissions and our own epistemic defects (Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%